Surgical Management of Postpartum Perineal and Rectovaginal Injuries - Naseem Saba, Muhammad Hamayun Khan, Neelam Mehsood, Sobia Rashid, Momina Ali Khan, Momin Ali Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Postpartum perineal and rectovaginal injuries are common complications of vaginal childbirth, ranging from minor tears to severe lacerations involving the anal sphincter complex and rectal mucosa. If not properly managed, these injuries can lead to long-term complications including fecal incontinence, pain during intercourse, and psychological distress. Surgical repair is essential to restore anatomical integrity, preserve continence, and optimize functional recovery. Methods: A two-year prospective observational study was conducted at a tertiary care hospital. Women aged 18–45 with third- or fourth-degree perineal tears or rectovaginal fistulas were included. Preoperative assessment included history, examination, and imaging if needed. Surgical repair involved layered closure of perineal structures, fistula repair, and sphincter reconstruction using end-to-end or overlapping techniques. Postoperative care included antibiotics, analgesia, stool softeners, and pelvic floor physiotherapy. Outcomes were assessed at one week, six weeks, and three months. Results: Among 120 patients, primary layered repair was performed in 67%, flap reconstruction in 21%, fistula repair in 4%, and secondary repairs in 8%. Complete recovery occurred in 83% of patients, and 92% reported satisfaction. Complications were infrequent, including infection (8%), wound dehiscence (4%), and urinary incontinence (4%). Early pelvic floor rehabilitation improved continence and functional outcomes. Rectovaginal fistula repairs showed good anatomical restoration with minimal recurrence. Overall, structured surgical repair with comprehensive postoperative care resulted in high recovery rates and patient satisfaction. Conclusion: Surgical repair combined with comprehensive postoperative care effectively restores anatomy and function, while structured rehabilitation and follow-up optimize recovery and reduce long-term morbidity. Keywords: Perineal injuries, Rectovaginal fistula, Postpartum repair, Surgical management.